Irrigation in Endodontics: Polyhexanide Is a Promising Antibacterial Polymer in Root Canal Treatment - Zurab Khabadze; Yulia Generalova; Alena Kulikova; Irina Podoprigora; Saida Abdulkerimova; Yusup Bakaev; Mariya Makeeva; Marina Dashtieva; Mariya Balashova; Fakhri Gadzhiev; Oleg Mordanov; Adam Umarov; et al. (MDPI AG, 2023)
Background:chronic apical periodontitis is a common pathology in dentistry, especially in endodontics. It is necessary to systematize data concerning commonly used irrigation solutions. The development of new protocols for endodontic treatment is a very promising direction. The use of a polyhexanide-based antiseptic can positively affect the results of endodontic treatment. Methods: the review was carried out involving the search for English language research and meta-analyses in the Google Scholar and PubMed databases. Results: the number of literary sources that were identified during the literature review is 180. After excluding publications that did not match the search criteria, the total number of articles included in the systematic review was determined to be 68. Conclusions: polyhexanide is a promising solution for infected root canal irrigation. The antibacterial activity of this substance is suitable for the elimination of pathogens responsible for the appearance of apical periodontitis.